Ethics of Information Technology in the Context of a Global Worldview - Didmanidze, Ibraim; Bagrationi, Irma (Моделювання, керування та інформаційні технології, 2021)
The present scientific paper outlines in today’s contemporary world - where everything is as it seems at first glance, subordinated to the economy, technology and politics are essentially ruled by ethics, value attitudes, which in that or otherwise find embodiment for purposes activities. After all, the question of goals, intentions is the question about values. The paper underlines that modern information technology has sharpened the problem of the values of the human spirit and choice further path of our world civilization. Everyone remembers the 20th century with its socio-cultural contradictions. And the scale of the achievements, and the scale of destruction committed by people in the twentieth century, incomparable with any other times in its history. The present paper emphasizes that if we want to keep human moral values in the information sphere, then is the technology itself sufficient for this, creating suitable programs forcing save them? Of course, working in networks and not consider off-grid the laws impossible. The paper concludes that what will this process lead to, hard to say. One thing is clear now: interacting with a digital computer, we inevitably become different. Society becomes others. And to regret it is nostalgia for past, it is sweet - meaningless. Like us modern peace or not - but this is reality life, and of them desirable proceed if we want to impact on construction our future